The relationship between immun staining and progression markers in IgA nephropathy - Karahisar Şirali, Semahat; Büberci, Refika (The European Research Journal, 2024)
Objective: To determine the relationship between immunofluorescence microscopy findings and progression markers at the time of diagnosis in immunoglobulin A (IgA) nephropathy. Methods: Fifty-two patients with pathological diagnosis of primary IgA nephropathy by showing mesangial and mesangiocapillary IgA-dominant immune deposits in immunofluorescence microscopy were included in the study. At the time of biopsy, biochemical and hematological data, Oxford MEST score and immunofluorescent staining findings were recorded. The serum IgA/C3 ratio was calculated. The immunofluorescence results of the total group were compared with the markers of progression at the time of diagnosis, estimated glomerular filtration rate (eGFR), hematuria, proteinuria, creatinine, and serum IgA/C3 ratio. Results: The mean age of the study group was 39.9±12.3 years and 55.8% were male. eGFR, albumin, hemoglobin, IgM were significantly lower, and uric acid and hematuria were significantly higher in those with proteinuria above 1 g compared to those with low proteinuria. A positive correlation was found between IgA, C3 and lambda staining and hematuria. There was a positive correlation between C3 staining and creatinine, and a positive correlation with hematuria. A correlation was found between Kappa staining and eGFR. Conclusion: Correlation was found between IgA, C3 and lambda staining and hematuria at the time of diagnosis in IgA nephropathy.